Measuring the dosage of brief and skill-targeted social-emotional learning (SEL) activities in humanitarian settings - Wu, Zezhen; Brown, Lindsay; Kim, Ha Yeon; Yoshikawa, Hirokazu; Aber, J. Lawrence (Frontiers in Psychology, 2023)
In this study, we propose and evaluate measures for three dimensions of dosage (quantity, duration, temporal pattern) of two sets of brief and skill-targeted social-emotional learning (SEL) activities (Mindfulness and Brain Games) implemented in 20 primary schools in two low-income chiefdoms of Sierra Leone. We find preliminary evidence of predictive validity that these dosage measures could predict children’s attendance and classroom adaptive behavior. This study is the first to develop procedures to measure dimensions of dosage of brief SEL activities in humanitarian settings. Our findings illuminate the need for future research on optimizing the dosage and implementation design of SEL programming using brief SEL activities.